Anticholinergic and sedative medication use in older community‐dwelling people: A national population study in the Netherlands. Issue 3 (12th February 2019) - van der Meer, Helene G.; Taxis, Katja; Teichert, Martina; Griens, Fabiënne; Pont, Lisa G.; Wouters, Hans
Abstract: Purpose: To identify the proportion of older adults with a high anticholinergic/sedative load and to identify patient subgroups based on type of central nervous system (CNS)‐active medication used. Methods: A cross‐sectional study of a nationwide sample of patients with anticholinergic/sedative medications dispensed by 1779 community pharmacies in the Netherlands (90% of all community pharmacies) in November 2016 was conducted. Patients aged older than 65 years with a high anticholinergic/sedative load defined as having a drug burden index (DBI) greater than 1 were included. Proportion of patients with a high anticholinergic/sedative load was calculated by dividing the number of individuals in our study population by the 2.4 million older patients using medications dispensed from study pharmacies. Patient subgroups based on type of CNS‐active medications used were identified with latent class analysis. Results: Overall, 8.7% (209 472 individuals) of older adults using medications had a DBI greater than 1. Latent class analysis identified four patient subgroups (classes) based on the following types of CNS‐active medications used: "combined psycholeptic/psychoanaleptic medication" (class 1, 57.9%), "analgesics" (class 2, 17.9%), "antiepileptic medication" (class 3, 17.8%), and "anti‐Parkinson medication" (class 4, 6.3%). Conclusions: A large proportion of older adults in the Netherlands had a high anticholinergic/sedative load. Four distinct subgroups using specific CNS‐active medication were identified. Interventions aiming at reducing the overall anticholinergic/sedative load should be tailored to these subgroups.